Photoelasticity raycasting - Bußler, Michael; Ertl, Thomas; Sadlo, Filip (Computer graphics forum, 2015)
We present a novel physically-based method to visualize stress tensor fields. By incorporating photoelasticity into traditional raycasting and extending it with reflection and refraction, taking into account polarization, we obtain the virtual counterpart to traditional experimental polariscopes. This allows us to provide photoelastic analysis of stress tensor fields in arbitrary domains. In our model, the optical material properties, such as stress-optic coefficient and refractive index, can either be chosen in compliance with the subject under investigation, or, in case of stress problems that do not model optical properties or that are not transparent, be chosen according to known or even new transparent materials. This enables direct application of established polariscope methodology together with respective interpretation. Using a GPU-based implementation, we compare our technique to experimental data, and demonstrate its utility with several simulated datasets.
Gesehen am 30.10.2020